Multistimuli‐Responsive Luminescence of Naphthalazine Based on Aggregation‐Induced Emission. Issue 4 (13th April 2015) - Yao, Xiang; Ru, Jia‐Xi; Xu, Cong; Liu, Ya‐Ming; Dou, Wei; Tang, Xiao‐Liang; Zhang, Guo‐Lin; Liu, Wei‐Sheng
Abstract Stimuli‐responsive luminescent materials, which are dependent on changes in physical molecular packing modes, have attracted more and more interest over the past ten years. In this study, 2, 2‐dihydroxy‐1, 1‐naphthalazine was synthesized and shown to exhibit different fluorescence emission in solution and solid states with characteristic aggregation‐induced emission (AIE) properties. A remarkable change in the fluorescence of 2, 2‐dihydroxy‐1, 1‐naphthalazine occurred upon mechanical grinding, heating, or exposure to solvents. According to the characterization by solid‐state fluorescence spectroscopy, X‐ray crystallography, differential scanning calorimetry, and X‐ray powder diffraction, the fluorescence change could be attributed to transitions between two structurally different polymorphs. These significant properties could also give 2, 2‐dihydroxy‐1, 1‐naphthalazine more potential applications as a multifunctional material.